Morphological and Chemical Changes in the Hemolymph of the Wax Moth Galleria mellonella Infected by the Entomopathogenic Fungus Conidiobolus coronatus - Mieczysława Irena Boguś; Agata Kaczmarek; Anna Katarzyna Wrońska; Mikołaj Drozdowski; Lena Siecińska; Ewelina Mokijewska; Marek Gołębiowski (Pathogens)
Hemolymph enables communication between organs in insects and ensures necessary coordination and homeostasis. Its composition can provide important information about the physiological state of an insect and can have diagnostic significance, which might be particularly important in the case of harmful insects subjected to biological control. Galleria mellonella Linnaeus 1758 (Lepidoptera: Pyralidae) is a global pest to honey bee colonies. The hemolymph of its larvae was examined after infection with the soil fungus Conidiobolus coronatus (Constantin) Batko 1964 (Entomophthorales). It was found that after one hour of contact with the fungus, the volume of the hemolymph increased while its total protein content decreased. In larvae with a high pathogen load, just before death, hemolymph volume decreased to nearly initial levels, while total protein content and synthesis (incorporation of 35S-labeled methionine) increased. The hemolymph polypeptide profile (SDS-PAGE followed by autoradiography) of infected insects was significantly different from that of healthy larvae. Hemocytes of infected larvae did not surround the fungal hyphae, although they encapsulated small foreign bodies (phase contrast microscopy). Infection had a negative effect on hemocytes, causing oenocyte and spherulocyte deformation, granulocyte degranulation, plasmatocyte vacuolization, and hemocyte disintegration. GC-MS analysis revealed the presence of 21 compounds in the hemolymph of control insects. C. coronatus infection caused the appearance of 5 fatty acids absent in healthy larvae (heptanoic, decanoic, adipic, suberic, tridecanoic), the disappearance of 4 compounds (monopalmitoylglycerol, monooleoylglycerol, monostearin, and cholesterol), and changes in the concentrations of 8 compounds. It remains an open question whether substances appearing in the hemolymph of infected insects are a product of the fungus or if they are released from the insect tissues damaged by the growing hyphae.